2015
DOI: 10.1016/j.mjafi.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of molecular subtypes of invasive breast cancer: A retrospective study

Abstract: a b s t r a c tBackground: Classification of breast cancers into different molecular subtypes using immunohistochemistry as a surrogate tool to DNA microarray technology has been identified. Aim of this study was to find the precise prevalence of molecular subtypes of invasive breast carcinoma using immunohistochemistry and to correlate it with histological and clinical prognostic factors.Methods: A descriptive study design wherein 56 breast carcinoma cases diagnosed between May 2012 and Apr 2014 were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
23
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 17 publications
(10 reference statements)
11
23
2
3
Order By: Relevance
“…This disagrees with other studies from India where 34% of the cases were luminal A, followed by TNBC (25%); whereas luminal B and Her2/neu subtypes had same prevalence (18% of each) [41]. Studies in Ghana indicated 25.6% of luminal A, 12.2% of luminal B and 49.9% of TNBC (27).…”
Section: Discussioncontrasting
confidence: 88%
“…This disagrees with other studies from India where 34% of the cases were luminal A, followed by TNBC (25%); whereas luminal B and Her2/neu subtypes had same prevalence (18% of each) [41]. Studies in Ghana indicated 25.6% of luminal A, 12.2% of luminal B and 49.9% of TNBC (27).…”
Section: Discussioncontrasting
confidence: 88%
“…9.0%, and TN 17.7% versus 16.5%, respectively. Two studies from India demonstrated fewer luminal types: luminal A 43.8% and 34%, luminal B 14.8% and 18%, Her2 overexpression 16.1% and 18%, TN 25.3% and 25% . Data from Switzerland and Germany included more patients with luminal types, especially luminal A, which seemed to offer a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The basal-like tumors make up the biggest part of the group of TNT (70%-90%), while the rest are non basal-like. The basal-like subtype represents a homogeneous group of tumors sharing a common genetic profile, treatment response and prediction of the course of illness 5,11,13,14 . So far, there has not been enough information about difference in the malignant potential of TNT considering the origin of cancer cells, and the question being posed is whether differences in the prognosis and treatment among a small share of patients with triple negative cancer are a result of the malignant potential within the TNT considering their basal-like and non basal-like origin.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, increasing the number of markers increases the test specificity and sensitivity 10 . However, as there is no general consensus on the criteria for identifying basal-like tumors through immunohistochemical analysis, it is recommendable to use a limited number of markers, such as CK 5/6, CK 14, CK 17, P-cadherin and EGFR 5,11 . The immunohistochemical reaction was positive for CK 5/6 in 37%, for CK14 in 50.86% and for P-cadherin in 68.34% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation